Pengaruh Kondisi Keuangan, Struktur Modal, Ukuran Perusahaan Dan Modal Kerja Terhadap Profitabilitas Pada Perusahaan Financial Di Bei Periode 2016 – 2019 - Jeselin Jeselin; Elly Tashia; Wenny Anggeresia Ginting (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
Analyze the influence of financial conditions, capital structure, firm size and working capital onProfitability of Financial Companies on the IDX for the 2016 – 2019 period. The research approach used is a quantitative approach. The sampling method is purposive sampling, a sample of 46 financial companies on the Indonesia Stock Exchange for the period 2016 – 2019. The results show the debt to equity ratio, current ratio, ln total assets, and working capital have a simultaneous and significant effect on return on assets in financial companies. on the IDX for the period 2016 – 2019. Debt to equity ratio has an effect and partially significant to the return on assets of financial companies on the IDX for the 2016 – 2019 period. The current ratio has a partial and significant effect on the return on assets of financial companies on the IDX for the 2016 – 2019 period. Ln total assets have a partial and significant effect on the return on assets in Financial Companies on the IDX for the 2016 – 2019 period. Working capital has a partial and significant effect on the return on assets of Financial Companies on the IDX for the 2016 – 2019